8.19 THE IMPACT OF INVESTMENTS ON THE ECONOMY OF THE REPUBLIC OF UZBEKISTAN AND THE IMPORTANCE OF ITS GEOGRAPHICAL LOCATION - To‘rayev Diyorbek O‘ktamovich (Innovative technologies in construction Scientific Journal, 2024)
В данной статье рассматриваются инвестиционные процессы после того, как Республика Узбекистан стала независимым государством, в том числе роль и эффективность инвестиций в государстве. Кроме того, перечислены основные факторы развития и модернизации экономики страны, показаны современные глобальные факторы и то, как формируются иностранные инвестиции в Республике. В конце статьи анализируются некоторые меры по совершенствованию инвестиционной политики государства. Ключевые слова: экономика Республики Узбекистан, инвестиции, динамика экономического роста, принципы корпоративного управления, меры. Annotation: This article presents investment processes after the Republic of Uzbekistan became an independent state, which cover the role and effectiveness of investments in the state. In addition, the main factors of development and modernization of the country's economy are listed, modern global factors and ways of forming foreign investments in the republic are indicated. At the end of the article, a number of measures to improve the investment policy of the state were analyzed. Keywords: economy of the Republic of Uzbekistan, investments, investments, dynamics of economic growth, principles of corporate governance, measures. After gaining independence in 1991, the Republic of Uzbekistan decided to conduct an independent foreign economic policy aimed at achieving real openness of the economy and integrating it into the world economic system. The participation of the Republic of Uzbekistan in international cooperation is determined by natural, economic, cultural, historical and other opportunities. Innovative investments are important nowadays. They will help to improve the real sector of the country's economy and form a new quality foundation for stable, long-term development of the economy. The main factor for the development and modernization of the country's economy is the creation of a favorable investment environment, encouraging the business community to invest heavily in industry and high-tech production. Market processes are intensifying against the background of the growth of local production and high investment activity. The main goal of the investment policy is to develop investment activities that help improve the country's economy and increase the efficiency of social production.